Phytochemical Profiling and Biological Assessment of Lantana camara Extracts: In Vitro Evaluation of Cytotoxicity and Anti-inflammatory Activities (International Journal of Scientific Research in Science and Technology, 2026)
The present study investigates the phytochemical composition and in vitro biological activities of solvent-specific extracts of Lantana camara. Petroleum ether, methanol and aqueous extracts were prepared using Soxhlet and microwaveassisted extraction methods, respectively, and characterized by FT-IR, and GC–MS analysis. The anticancer potential was evaluated against human hepatocellular carcinoma (HepG2) cells using the MTT assay, while anti-inflammatory activity was assessed through the hemolysis inhibition (membrane stabilization) assay. The petroleum ether extract exhibited potent cytotoxic activity with an IC₅₀ value below 100 µg/mL, indicating strong anticancer potential. In contrast, the aqueous extract showed comparatively lower cytotoxicity but demonstrated significant antiinflammatory activity, with marked inhibition of protein denaturation and effective membrane stabilization. These findings highlight a clear solvent-dependent structure–activity relationship and support the therapeutic potential of Lantana camara as a source of complementary anticancer and anti-inflammatory agents.